Consulting report – Transgas Shipping Lines - López Mata, Rodner Nilver (2017)
Transgas Shipping Lines S.A. is a Peruvian shipping company specializing in the Maritime transport of Liquefied Petroleum Gas, Crude Oil and by-products, and Chemical products. In 1991, the company began to transport LPG between Peruvian ports. Seven years later, they began to conquer international markets, reaching important places on the West Coast of South America, the Caribbean region and some countries of the Asian continent. This is an example that as time goes on, the market becomes more competitive and new challenges arise, where companies have to respond with new strategies. In this sense, Transgas seeks to improve its performance not only in the core areas, but also within the support departments such as a logistics and operations department. After the analysis of the company’s current situation, the main problem has been defined as the ineffective control, management and measurement of the logistics and operations department. The qualitative and quantitative analysis of this problem concludes that the company is affected in different activities within the organization. At the same time, the company presents economic losses and decrease in the income statement due to low efficiency and the ignorance of the current performance. The solution presented in this report has a set of steps to follow which has as a final product the elaboration of a dashboard, where the Key performance indicators of the department in the study will be shown. The implementation of this project consists of 4 phases which start with the change of culture, followed by the redefinition of the processes, the systematization of information and finally the creation of the dashboard. This implementation will allow the company to measure its performance, control its processes and thus improve its operations, with the aim of providing a high-quality service to their clients. The total investment for this project of 38 weeks was calculated to be S/. 28,000 soles